Die Schirmherrschaft. - Becker, Wolfgang; Voss, Anne Katrin (Aachen : NAK - Neuer Aachener Kunstverein, 1987)
Eisenegger, René ; Häberli, Markus ; Schwyn, Eduard ; Wäckerlin, Christian ; Jahn, Heinz ; Möckel, Ulli ; Mussenbrock, Hajo ; Pietryga, Stephan ; Unger, Thomas ; Falken, Herbert ; Linssen, Jupp ; Altgassen, Bernd ; Müller-Drehsen, Renate
biografie
Die Schirmherrschaft, in Räumen der Schirmfabrik Brauer, Aachen, 26.5. - 30.6.87
Duits
boek